Dizeres sobre o Programa de Mobilidade Internacional na formação do professor de língua estrangeira - Souza, Danúbia Fábia de (2016)
This thesis was elaborated from an inter/transdisciplinary approach that includes Applied Linguistics (AL), Dialogical Discourse Analysis (DDA) and French Line Discourse Analysis (DA). The developed research had as purpose to analyze how abroad experience and International Mobility Program (IMP) participation are discursively represented by the individuals when they occupy the discursive place of (future) Foreign Languages (FL) teachers. This means that we aim to investigate how the abroad experience faced by these individuals can influence their academic education and their professional practice. Regarding the research participants, we analyzed how four (04) pre-service or in-service FLs teachers (English and French) who participated in the program, representing IMP, contact with FL abroad and FL learning teaching process. These four teachers testimonials were collected through the AREDA Proposal (Analysis of Discursive Resonances in Open Testimonials) (SERRANI-INFANTE, 1998). As a result, it was possible to realize that the relation of the research participants in concerning to the experience faced in the IMP is marked by three representations, which are: i) representing IMP; ii) representing the contact with abroad FL; iii) representing FL teaching-learning process. These representations interpenetrate and interconstitute themselves, and the built discursiveness in some of enunciators sayings beckons for some discursive inscriptions, namely: i) the IMP inscription as reference for FL teacher formation and the inscription in the (illusion) of completeness (IMP representing); ii) excellence speech inscription and completeness of the other (representing the contact with the FL abroad); iii) enrollment in PMI as a reference for learning and teaching (representing the teaching-learning process of FL). Therefore, in order to place IPM influence in its academic education and in its professional practice, the teachers discursively register themselves in order to represent the IMP from the socio-historical-ideological-discursive place they occupy. The dialogue established by the discursive inscriptions reveals the positioning of those individuals who build an imaginary place for IMP, in order to represent it discursively as essential/fundamental for FL teaching and learning and for FL teacher formation and practice, in other words, there is an inscription in the IMP's supremacy discourse for FL teacher’s constitution.